Multiple blanking preprocessors for impulsive noise mitigation in OFDM-based power-line communication systems - Liong, A.A.G.; Juwono, Filbert Hilman; Gopal, Lenin; Chiong, C.W.R.; Rong, Yue (ELSEVIER SCI LTD, 2021)
Power-line communication (PLC) technology has been a critical enabler for smart grid systems. It provides two-way communication links without new infrastructure deployment. However, as the power-line was not designed to carry data, there are many drawbacks when it is used as a communication channel. One of the major drawbacks is impulsive noise occurrence. Blanking nonlinear preprocessor has been commonly used for mitigating impulsive noise in orthogonal frequency-division multiplexing (OFDM)-based PLC. It uses a threshold to detect whether a signal sample is contaminated by impulsive noise. Optimum performance is obtained when the optimal blanking threshold is used. The optimal blanking threshold depends on noise parameters, which are usually assumed to be available to the receiver. However, they may not be known in practice. In this paper, we propose a blanking preprocessor bank consisting of multiple blanking preprocessors with different thresholds which blindly handles the impulsive noise. Each blanking preprocessor is considered to provide an independent channel. The output of all preprocessors is combined using the maximal ratio combining (MRC) technique at the OFDM demodulator. Simulation results show that the proposed blanking preprocessor bank method results in better performance compared to the one using the optimal threshold method.